Web site design for people with dementia - Savitch, Nada; Zaphiris, Panayiotis (My University, 2007)
This chapter describes the current thinking around designing Web sites for people with dementia. It is important that people with dementia are involved in the development of Web sites that are designed for them to use. The chapter offers advice for both researchers and practitioners who may not have thought about this user group. Symptoms of dementia are described, and the design needs of people with the condition are discussed. A list of design considerations for Web site designers covering simplified displays, avoiding distractions, consistent and familiar page design, contextual support, the use of colour, graphics, icons and sound, language and content, and navigation and menus is presented. Appropriate methodologies for working with people with dementia are also described.